1977
DOI: 10.1093/ajcp/67.5.462
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Factor VIII-related Antigen Using Commercial Antisera

Abstract: Commercially available antiserum to factor VIII was used in several tests to determine whether it might serve as a reference between research laboratories involved in investigation of the factor VIII complex and whether the antiserum might be useful in the screening of large populations of patients with hereditary disorders of factor VIII. In Ouchterlony plates, the antiserum gave a single line of identity with concentrated factor VIII, cryoprecipitate, and human plasma. The antiserum was capable of inhibiting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1977
1977
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Recovery may vary according to the factor VIII product, the patient and the estimation of factor VIII dose. This study confirms the findings which showed similar recovery with factor VIII concentrates of various purity [26,39], Pre vious studies have shown large variations in recovery from patient to patient [1,2,6,10,34]. The recovery of F VIII:C was not sig nificantly related to the clinical state of the bleeding or nonbleeding patient [1].…”
Section: Discussionsupporting
confidence: 89%
“…Recovery may vary according to the factor VIII product, the patient and the estimation of factor VIII dose. This study confirms the findings which showed similar recovery with factor VIII concentrates of various purity [26,39], Pre vious studies have shown large variations in recovery from patient to patient [1,2,6,10,34]. The recovery of F VIII:C was not sig nificantly related to the clinical state of the bleeding or nonbleeding patient [1].…”
Section: Discussionsupporting
confidence: 89%
“…The stored PPP supernatants were used to determine the concentration of von Willebrand factor antigen (VWF: Ag) and von Wllebrand factor functionally assayed as ristocetin cofactor (RiCof). Von Willebrand factor antigen was measured using a commercial antibody (12) following the Laurell technique (13). The electrophoretic mobility of VWF:Ag was done by cross immunoelectrophoresis (CIE) using the same commercial antibody and a modification of the technique described by Sultan et al (14).…”
Section: Methodsmentioning
confidence: 99%